Herpesvirus ateles DNA and Its Homology with Herpesvirus saimiri Nucleic Acid - Fleckenstein, Bernhard (1978)
Analysis of the structural organization of Herpesvirus ateles DNA shows that two types of viral DNA molecules are encapsidated in virions: (i) M-genomes, which contain 74% light sequences (L-DNA, 38% guanine plus cytosine) and 26% highly repetitive heavy sequences (H-DNA, 75% guanine plus cytosine), and (ii) defective H-genomes, which consist exclusively of repetitive H-DNA. The structure of M-genomes from H. ateles consists of an L-DNA region of about 70 × 10(6) daltons inserted between H-DNA termini of variable length. M-genomes with a shorter H-DNA region at one end of the molecule have a long stretch of H-DNA at the other end, resulting in a total molecular weight of 89.8 ± 8.5 × 10(6). Thus it resembles the structure of M-genomes of H. saimiri. H-DNA of the two independent H. ateles isolates, strains 810 and 73, reveals different patterns after cleavage with restriction endonuclease Sma I. H-DNA of H. ateles 810 appears to consist of identical tandem repeat units with a molecular weight of 1,035,000; the H-DNA repeat unit of strain 73 is shorter (930,000 molecular weight). Corresponding DNA sequences of the two H. ateles strains (810 and 73) are completely homologous in cross-hybridizations. However, a discrete nucleotide sequence divergence between these virus strains is detected by measuring melting temperatures (T(m)) of DNA hybrid molecules. Some homology exists between H. ateles and H. saimiri DNA. Hybridization of L-DNA from H. ateles with L-DNA from H. saimiri shows about a 35% homology between the respective L-DNA sequences; the resulting heteroduplex molecules show a decrease of T(m) by 13.5°C, corresponding to about a 9% mismatching in cross-hybridizing parts of L-regions. Very little homology is found between H-DNA of H. ateles and H. saimiri.